Mental cost in higher education: a comparative study on academic stress as a predictor of mental health in university students during and after the COVID-19 pandemic - Patricia Gasser; Alberto Grajeda; Juan Pablo Cordova; Isabel La Fuente; Pamela Cordova; Hernán Naranjo; Alberto Sanjinés (Cogent Education)
This study examines the incidence of academic stress and its determinants on mental health among university students. It employs a comparative approach to evaluate the role of academic stress as a predictor of mental health outcomes during and after the COVID-19 pandemic. Utilizing a mixed-methods approach, the research surveyed students using standardized instruments to measure academic stress and mental health. Cross-sectional analyses were conducted at two time points, drawing on responses from undergraduate students at a private university in Latin America. The primary objectives were to quantify academic stress levels and their stressors, evaluate mental health status, and explore this relationship during these periods. Data collection yielded 1,265 and 707 valid responses for each respective period, employing the Academic Stress Inventory and the Mental Health Continuum-Short Form for assessments. Findings indicated high stress levels among students, regardless of the pandemic phase, with notable stressors including teacher, exam, results, group work, peer, time management, and self-inflicted stress. The post-pandemic phase revealed changes in the impacts of stressors, with self-inflicted stress, group work, and time management stress showing significant relevance to mental health. The study highlights the challenge of academic stress on mental health, urging educational institutions to address pressures and provide support mechanisms for student well-being.